2022
DOI: 10.37284/eajhs.5.1.698
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, Opportunities, and Strategies for Addressing Drugs and Substance Abuse in Selected Counties in Kenya

Abstract: Introduction: Drugs and substance abuse is one of the most pervasive problems in Kenya placing a great economic, social, and health burden on the society. If left unaddressed, the country risks losing generations and development opportunities due to the diversion of resources to address the problem. Therefore in lieu of the complexities of drugs and substance abuse, difficulties, and cost of treatment, the development of effective treatment and prevention programs is a crucial part of a public health system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Our results are comparable to an earlier descriptive studies in Uganda, that found PWID to be predominatly male, not married, with some earning a living through sex work (19). Similar findings have been reported in other regions, highlighting the vulnerability of unemployed and economically disadvantaged populations to injecting drug use (20,21). The UNODC resource guide on counseling in targeted intervention for injecting drug users, emphasizes the importance of understanding the characterisitics of IDU, for the successful management of opioid use disorder.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are comparable to an earlier descriptive studies in Uganda, that found PWID to be predominatly male, not married, with some earning a living through sex work (19). Similar findings have been reported in other regions, highlighting the vulnerability of unemployed and economically disadvantaged populations to injecting drug use (20,21). The UNODC resource guide on counseling in targeted intervention for injecting drug users, emphasizes the importance of understanding the characterisitics of IDU, for the successful management of opioid use disorder.…”
Section: Discussionsupporting
confidence: 90%